(untitled) (Research, Society and Development, 2020)
Objective: To analyze the use of different Information and Communication Technologies for dissemination of public information about COVID-19 in the Southeastern region of the Brazil. Method: Cross-sectional study carried out between July and August of 2020 with 2,477 residents from southeastern Brazil. The instrument was made available online through social networks. Descriptive statistics with chi-square test and Fisher’s exact test were used for data analysis. Results: All types of communication channels analyzed differed significantly according to gender and monthly family income. Respondents aged 18 to 39 received information from COVID-19 through social media, WhatsApp and Youtube videos. Conclusion: We identified a predominance of women aged between 18 to 39 years and monthly income of 2 to 4 minimum wages, who received information about COVID-19 through traditional media. However, most participants would like to receive information and answer questions from COVID-19 via WhatsApp, an Information and Communication Technology that should be used and evaluated by researchers and health authorities for COVID-19 risks communication.